PRENATAL INFECTION, MATERNAL IMMUNE ACTIVATION, AND RISK FOR SCHIZOPHRENIA - Canetta, Sarah E. (2012)
A body of epidemiological literature has suggested an association between prenatal infection, subsequent maternal immune activation (MIA), and later risk of schizophrenia. These epidemiological studies have inspired preclinical research using rodent and primate models of prenatal infection and MIA. The findings from these preclinical studies indicate that severe infection and immune activation during pregnancy can negatively impact offspring brain development and impair adult behavior. This review aims to summarize the major epidemiological and preclinical findings addressing the connection between prenatal infection and immune activation and later risk of developing schizophrenia, as well as the more limited literature addressing the mechanisms by which this gestational insult might affect offspring neurodevelopment. Finally, directions for future research will be discussed.